2019
DOI: 10.1111/bdi.12796
|View full text |Cite
|
Sign up to set email alerts
|

Is smartphone‐based mood instability associated with stress, quality of life, and functioning in bipolar disorder?

Abstract: Objective Mood instability in patients with bipolar disorder has been associated with impaired functioning and risk of relapse. The present study aimed to investigate whether increased mood instability is associated with increased perceived stress and impaired quality of life and functioning in patients with bipolar disorder. Methods A total of 84 patients with bipolar disorder used a smartphone‐based self‐monitoring system on a daily basis for 9 months. Data on perceived stress, quality of life, and clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…For example, ulceration is exacerbated during examination periods and lessened during periods of vacation for students (Scully, 2013). Meanwhile, stress is well known to correlate with mood instability and subjective wellbeing (Schneiderman et al, 2005;Atanes et al, 2015;Berrios et al, 2016;Gillett and Crisp, 2017;Faurholt-Jepsen et al, 2019). Our study suggested that mood instability and subjective wellbeing are causally associated with mouth ulcers using several MR methods.…”
Section: Discussionmentioning
confidence: 57%
“…For example, ulceration is exacerbated during examination periods and lessened during periods of vacation for students (Scully, 2013). Meanwhile, stress is well known to correlate with mood instability and subjective wellbeing (Schneiderman et al, 2005;Atanes et al, 2015;Berrios et al, 2016;Gillett and Crisp, 2017;Faurholt-Jepsen et al, 2019). Our study suggested that mood instability and subjective wellbeing are causally associated with mouth ulcers using several MR methods.…”
Section: Discussionmentioning
confidence: 57%
“…The core content elements of psychoeducation (to be delivered to all patients) are the content elements shared across the psychological treatments, including improved ability to recognise early warning signs, knowledge about and acceptance of BD, and daily monitoring of mood and sleep (Duffy et al, 2019; Faurholt-Jepsen et al, 2019) (see Table 22 in MDcpg 2015 ). These elements are often conceptualised as part of self-management approaches to BD (Gliddon et al, 2017; Michalak et al, 2019).…”
Section: Treatmentsmentioning
confidence: 99%
“…Smartphone-based self-monitored data have shown to validly reflect illness activity in patients with BD [15,21,[36][37][38]. Thus, smartphone-based self-monitoring may improve the timeliness in monitoring symptoms, functioning, and fluctuations in symptoms, and might, therefore, be a promising supportive diagnostic tool in individuals where BD is suspected.…”
Section: Introductionmentioning
confidence: 99%